(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This paper attempts to examine the influence of gender on the buying decision-making styles of consumers in Odisha, an eastern state of India. A total of 151 respondents from four different regions of Odisha were chosen by using the Mall intercept method. The samples were classified into males and females on the basis of gender. Exploratory Factor Analysis was carried to identify the decision-making styles. t-test was employed to compare the shopping styles of males and females. Results indicate that differences in consumer shopping styles exist among the male and female consumers. Findings can be used by retailers in targeting different segments of shoppers based on gender demography and consumer decision-making styles in order to achieve competitive advantage in the era of retail market complexity. It is recommended that males and female gender should be viewed as distinct consumer segments, which may warrant differential marketing efforts.